Analisis Kelayakan Bisnis Usaha Roti Ceriwis sebagai Oleh-Oleh Khas Kota Batam - Dewi Purnamasari; Bambang Hendrawan (Politeknik Negeri Batam, 2013)
Bussiness feasibility study is needed to see a figure out of feasibility to run a business. The purpose of this study is to address whether the Roti Ceriwis is fisible or not as specially food from batam. Every aspect should be feasible to have a certain standard of value, but the assessment is not only done on one aspect only. Assessment to determine eligibility should be based on the several aspects. Method of analysis uses feasible analysis from various aspect such as market and marketing aspects, technical aspects, financial aspects, in addition sensitivities analysis also used to asses input of cost increase toward business feasibility. The results of this study showed that businesses Roti Ceriwis feasible and has very good prospects.